Outbreaks by canopy-feeding geometrid moth cause state-dependent shifts in understorey plant communities - Karlsen, Stein Rune; Jepsen, Jane Uhd; Odland, Arvid; Ims, Rolf Anker; Elvebakk, Arve (Oecologia, 2013)
The increased spread of insect outbreaks is among the most severe impacts of climate warming predicted for northern boreal forest ecosystems. Compound disturbances by insect herbivores can cause sharp transitions between vegetation states with implications for ecosystem productivity and climate feedbacks. By analysing vegetation plots prior to and immediately after a severe and widespread outbreak by geometrid moths in the birch forest- tundra ecotone, we document a shift in forest understorey community composition in response to the moth outbreak. Prior to the moth outbreak, the plots divided into two oligotrophic and one eutrophic plant community. The moth outbreak caused a vegetation state shift in the two oligotrophic communities, but only minor changes in the eutrophic community. In the spatially most widespread communities, oligotrophic dwarf shrub birch forest, dominance by the allelopathic dwarf shrub Empetrum nigrum ssp. hermaphroditum, was effectively broken and replaced by a community dominated by the graminoid Avenella flexuosa, in a manner qualitatively similar to the effect of wild fires in E. nigrum communities in coniferous boreal forest further south. As dominance by E. nigrum is associated with retrogressive succession the observed vegetation state shift has widespread implications for ecosystem productivity on a regional scale. Our findings reveal that the impact of moth outbreaks on the northern boreal birch forest system is highly initial-state dependent, and that the widespread oligotrophic communities have a low resistance to such disturbances. This provides a case for the notion that climate impacts on arctic and northern boreal vegetation may take place most abruptly when conveyed by changed dynamics of irruptive herbivores.